REGULATION AND APPLICATION OF FAIR USE DOCTRINE ON THE YOUTUBE PLATFORM: A COMPARATIVE STUDY OF INDONESIAN AND UNITED STATES LAWS - Nurhijriati, Nurhijriati; Kurniasari, Eka (Student Journal of International Law, 2023)
YouTube has implemented a fair use policy that allows YouTubers to reuse copyrighted material under certain categories and limitations without obtaining permission from the copyright owner. This policy aligns with the US Copyright Law of 1976, which provides clear parameters for fair use. However, Indonesia's copyright law takes a different approach to regulating videos uploaded to the YouTube platform and the fair use of copyrighted material, with less explicit restrictive parameters outlined in Articles 43 and 44 of Law No.28 of 2014. This research employs a normative legal method, utilizing library research and a comparative approach. The findings indicate that both countries adhere to the same international conventions and recognize fair use categories such as education, criticism, and knowledge in videos uploaded to the YouTube platform. Indonesia can learn from the United States' regulations, particularly the clearly defined parameters of limitation outlined in the US Copyright Act of 1976.